BODY IMAGE ATLET ANGKAT BERAT, ANGKAT BESI, DAN BINARAGA KOMITE OLAHRAGA NASIONAL INDONESIA (KONI) PROVINSI RIAU TAHUN 2015 - Rizky Annisa Mampanini; Yanti Ernalia; Miftah Azrin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTSporting achievements ASEAN decreased level of concern for athletes. Riau Province has not been a lot of achievement in national and even international level. To achieve optimal performance in every sport, there are some complete one of which is mental development. In terms of the development of mental or psychological aspect, confidence in body shape quite an important role in influencing the performance of athletes. The aim of this study to find out how the perception of heavy lifters, weightlifter, and bodybuilder Indonesian National Sports Committee (KONI) Riau Province about body image. This study method was a descriptive cross-sectional with total sampling technique. The results showed that the heavy lifters of 16 people, weightlifter 9 people, and bodybuilder 5 people. Mostly male athletes than female (70.0%), the average age was at the end of adolescent age 17-25 years (66.7%), had a Body Mass Index at most Overweight (33.3%), and mostly had normal body image (73.3%).Keywords: body image, heavy lifters, weightlifter, bodybuilder